Tablets and their manufacturing method

JP7652778B2Active Publication Date: 2025-03-27AYUMI PHARMA
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022534121
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-01-06
Filing Date
2021-07-02
Publication Date
2025-03-27
Estimated Expiration
2041-07-02

Smart Images

  • Figure 0007652778000008
    Figure 0007652778000008
  • Figure 0007652778000009
    Figure 0007652778000009
  • Figure 0007652778000010
    Figure 0007652778000010
Patent Text Reader

Abstract

The present invention addresses the problem of providing a tablet that includes a high concentration of acetaminophen, that elutes acetaminophen at a rate of at least 80% in fifteen minutes, and that can be manufactured by dry tableting. The present invention provides a tablet, containing acetaminophen with a median grain diameter in the range 100–350 μm, crystalline cellulose with a bulk density in the range 0.10–0.23 g / cm3, and disintegrants of at least two types, wherein: the disintegrants of at least two types are a disintegrant (a) of at least one type selected from the group consisting of crospovidone, croscarmellose sodium, and sodium starch glycolate, and a disintegrant (b) that is low-substituted hydroxypropylcellulose; and the acetaminophen content per tablet is at least 86% by weight.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to Japanese Patent Application No. 2020-115271, filed on July 3, 2020, and Japanese Patent Application No. 2021-000629, filed on January 6, 2021, the entire disclosures of which are hereby expressly incorporated by reference. The present invention relates to a tablet or pharmaceutical composition containing acetaminophen at a high concentration. Furthermore, the present invention relates to a method for producing said tablet. [Background technology]

[0002] Acetaminophen is an antipyretic and analgesic with few side effects, and is widely used by patients of all ages. For medical use, the dosage of acetaminophen is limited to a total of 4000 mg per day for adults to relieve pain from headaches, lower back pain, etc., and is orally administered at 300-1000 mg at a time, with an interval of at least 4-6 hours. Currently, acetaminophen tablets are available in 500 mg, 300 mg, and 200 mg tablets, depending on the amount of active ingredient.

[0003] Currently, the fluidized bed granulation method, which is a wet granulation method, is the most widely used method for the manufacture of pharmaceuticals (Patent Documents 1 and 2). In the fluidized bed granulation method, drugs and additives are usually fed into a fluidized bed granulation device and fluidized, and a binder solution or a binder solution in which the drug is dissolved or suspended is sprayed and added. In this method, granules suitable for tableting are obtained for drug particles with excellent fluidity, but drug particles with poor fluidity are finely divided, and if there is a difference between the particle size and weight of the drug and the additive, the content uniformity may be impaired. In that case, a relatively large amount of additives must be added to improve fluidity and moldability, and the tablets become large. In addition, the fluidized bed granulation method is a method in which granules are first prepared by wet granulation, and then lubricants and other agents are added and the tablets are tableted, resulting in a large number of manufacturing steps and a high manufacturing cost.

[0004] In contrast, the dry direct compression method only involves mixing powders and compressing them into tablets, so there are fewer steps and this leads to reduced manufacturing costs, but compared to the dry granulation method and wet granulation method that produce granules, the mixed powder has poor fluidity, so there are problems with weight variation and compression moldability. In particular, acetaminophen has extremely strong secondary cohesion forces due to intermolecular forces (van der Waals forces) and electrostatic charges, is a powder with extremely poor fluidity, and has a complex particle shape, so it has been thought that it is difficult to formulate acetaminophen using the dry direct compression method.

[0005] A method for producing an acetaminophen formulation by dry direct compression is described, for example, in Patent Document 3. Patent Document 3 discloses the use of unpulverized acetaminophen for the production of tablets, which includes a step of blending a dispersant, a lubricant and other additives with unpulverized acetaminophen, and a step of crushing and sieving the acetaminophen at least once before or after blending the additives to disperse and adhere the additives to the surfaces of the acetaminophen particles. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2013-216610 A [Patent Document 2] Special Publication No. 2015-63521 [Patent Document 3] Patent Document 1: JP 2018-90638 A The entire disclosures of Patent Documents 1 to 3 are hereby expressly incorporated by reference. Summary of the Invention [Problem to be solved by the invention]

[0007] Patent Document 3 describes a moisture control step of adding water using a spray bottle and mixing, and it is believed that moisture control is performed to increase tablet hardness. Furthermore, Patent Document 3 describes a method including a step of disintegrating and sieving at least once before or after the addition of additives to disperse and attach additives to the surface of acetaminophen particles, which has more steps than the simplest dry direct compression method of mixing the drug substance and additives and tableting them. Therefore, there is a need to develop acetaminophen tablets that can be manufactured by the simpler dry direct compression method.

[0008] In addition, because the price of acetaminophen is very low, the additives used in many tablets are more expensive. Therefore, it is important to contain acetaminophen at a high concentration and reduce the amount of additives in order to reduce manufacturing costs. From the perspective of compliance and adherence, it is also necessary to contain acetaminophen at a high concentration. Furthermore, acetaminophen tablets must meet the official dissolution test standard of a dissolution rate of 80% or more in 15 minutes, as specified in Part 3 of the Japanese Pharmacopoeia Extra-Drug Standards.

[0009] Therefore, the problem to be solved by the present invention is to provide a tablet which contains a high concentration of acetaminophen, has a dissolution rate of 80% or more of acetaminophen from the tablet within 15 minutes, and can be produced by dry direct compression, and to provide a method for producing the same. [Means for solving the problem]

[0010] Under the above-mentioned problem, the present inventors have conducted intensive research and found that a tablet containing acetaminophen at a high concentration and satisfying the dissolution test standard can be obtained by mixing an acetaminophen drug substance having a particle size within a predetermined range, a specific crystalline cellulose, and at least two kinds of disintegrants, and directly compressing the mixture into tablets. The present invention has been completed based on the above-mentioned findings.

[0011] That is, according to the present invention, the following inventions are provided. [1] Acetaminophen having a median particle size in the range of 100 to 350 μm; 0.10~0.23g / cm 3 Microcrystalline cellulose having a bulk density in the range of and at least two disintegrants, At least two disintegrants At least one disintegrant (a) selected from the group consisting of crospovidone, croscarmellose sodium and sodium starch glycolate; and A disintegrant (b) which is low-substituted hydroxypropyl cellulose; A tablet having an acetaminophen content of 86% by weight or more per tablet. [2] The tablet described in [1], having a tablet hardness of 50N or more. [3] A tablet according to [1] or [2], wherein each tablet contains 7.3% by weight or more of the above crystalline cellulose. [4] The tablet according to any one of [1] to [3], wherein the ratio of the disintegrant (a) among the at least two types of disintegrants contained in one tablet is 15 to 95% by weight. [5] The tablet according to any one of [1] to [4], wherein each tablet contains 1.0 to 4.0% by weight of disintegrants (a) and (b) in total. [6] A tablet according to any one of [1] to [5], in which the dissolution rate of acetaminophen is 80% or more in 15 minutes. [7] Acetaminophen having a median particle size in the range of 100 to 350 μm; 0.10~0.23g / cm 3 Microcrystalline cellulose having a bulk density in the range of with at least two disintegrants to obtain a powder mixture; and directly compressing the powder mixture to obtain tablets; At least two disintegrants At least one disintegrant (a) selected from the group consisting of crospovidone, croscarmellose sodium and sodium starch glycolate; and The method for producing a tablet according to any one of [1] to [6], wherein the disintegrant (b) is low-substituted hydroxypropyl cellulose. [8] Acetaminophen having a median particle size in the range of 100 to 350 μm; 0.10~0.23g / cm 3 Microcrystalline cellulose having a bulk density in the range of and at least two disintegrants, At least two disintegrants At least one disintegrant (a) selected from the group consisting of crospovidone, croscarmellose sodium and sodium starch glycolate; and A disintegrant (b) which is low-substituted hydroxypropyl cellulose; A pharmaceutical composition, wherein the content of acetaminophen in one dosage unit is 86% by weight or more. [9] The pharmaceutical composition according to [8], wherein the pharmaceutical composition is a tablet for oral administration and has a tablet hardness of 50 N or more.

[10] The pharmaceutical composition according to [8] or [9], wherein the crystalline cellulose is contained in an amount of 7.3% by weight or more per dosage unit.

[11] The pharmaceutical composition according to any one of [8] to

[10] , wherein the proportion of the disintegrant (a) in the at least two types of disintegrants contained in one dosage unit is 15 to 95% by weight.

[12] The pharmaceutical composition according to any one of [8] to

[11] , wherein the disintegrants (a) and (b) are contained in a total amount of 1.0 to 4.0% by weight per dosage unit.

[13] The pharmaceutical composition according to any one of [8] to

[12] , wherein the dissolution rate of acetaminophen is 80% or more in 15 minutes. Effect of the Invention

[0012] According to the present invention, it is possible to provide a tablet containing acetaminophen at a high concentration and having a dissolution rate of 80% or more in 15 minutes. In addition, according to the present invention, it is possible to provide a method for producing a tablet by using a dry direct compression method, which is simple and low in production cost. [Brief description of the drawings]

[0013] [Figure 1] 1 shows the dissolution curves of Tablet A1 and Tablet B produced in Example 1. The vertical axis represents the dissolution rate of acetaminophen, and the horizontal axis represents the time (min) for sampling the test liquid. [Diagram 2] FIG. 2 is a graph showing the relationship between the ratio of crospovidone in two types of disintegrants and the 15-minute dissolution rate (%). [Diagram 3] FIG. 3 is a graph showing the relationship between the ratio of crospovidone in two types of disintegrants, the acetaminophen (APAP) content, and the 15-minute dissolution rate (%). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, embodiments of the present invention will be described in detail. In this specification, a numerical range expressed using "to" means a range including the numerical values ​​before and after "to" as the lower and upper limits.

[0015] (tablet) The present invention relates to a pharmaceutical composition comprising acetaminophen having a median particle size in the range of 100 to 350 μm, 0.10~0.23g / cm 3 Microcrystalline cellulose having a bulk density in the range of and at least two disintegrants, At least two disintegrants At least one disintegrant (a) selected from the group consisting of crospovidone, croscarmellose sodium and sodium starch glycolate; and A disintegrant (b) which is low-substituted hydroxypropyl cellulose; The present invention relates to a tablet having an acetaminophen content of 86% by weight or more per tablet.

[0016] The physiologically active drug in the tablet of the present invention is acetaminophen. Acetaminophen is an antipyretic analgesic drug used as a symptomatic treatment for fever, chills, headache, etc. The tablet or pharmaceutical composition of the present invention contains a medicamentously effective amount of acetaminophen and can be orally administered to a patient in need of treatment therewith. The method of producing the tablet of the present invention will be described later.

[0017] The tablet of the present invention may be a normal tablet or an orally disintegrating tablet, preferably a normal tablet. The tablet of the present invention may be a plain tablet (compressed tablet) compressed by tableting or the like, or a coated tablet having a coating layer provided around the plain tablet, preferably a plain tablet.

[0018] The median particle size (D50) of the acetaminophen drug substance used in the tablet of the present invention (hereinafter referred to as the present acetaminophen drug substance) is in the range of 100 to 350 μm, preferably in the range of 120 to 330 μm. The particle size distribution of the present acetaminophen drug substance is such that D10 is in the range of 5 to 200 μm, preferably in the range of 10 to 170 μm, more preferably in the range of 20 to 150 μm, and D90 is in the range of 200 to 600 μm, preferably in the range of 250 to 550 μm, more preferably in the range of 250 to 530 μm. There may be some difference between production lots. In addition, the volume average particle size (MV) of the present acetaminophen drug substance can be in the range of 100 to 350 μm, and may be in the range of 120 to 330 μm. There may be some difference between production lots. In the present invention, the particle size distribution is determined by volume distribution evaluation using dry particle size measurement by laser diffraction method (Laser Micron Sizer LMS-2000e (Seishin Enterprise Co., Ltd.)), and D50 is the median particle size, which is the particle size at 50% cumulative volume from the small diameter side of the particle size distribution.

[0019] The present acetaminophen drug substance may be one that has not been subjected to any special treatment after crystallization, or one that has been sieved after crystallization. In one embodiment of the present invention, the present acetaminophen drug substance may be one that has not been subjected to pulverization after crystallization. In a preferred embodiment of the present invention, the present acetaminophen drug substance is one that has been sieved after crystallization. The sieving process is performed to obtain a powder containing more particles with a particle size suitable for the production of the tablet of the present invention. When a drug substance containing a large amount of coarse acetaminophen crystals (e.g., D50 of 400 μm or more) is used, it is considered that it is not possible to form a tablet due to poor disintegration. In addition, it is considered that it is difficult to form a tablet using a drug substance containing a large amount of acetaminophen fine particles (e.g., 30 μm or less). By sieving, coarse acetaminophen crystals and acetaminophen fine particles can be removed.

[0020] The acetaminophen content of the tablet of the present invention is 86% by weight or more. If the acetaminophen content is 86% by weight or more, the tablet will not be excessively large even if 200 to 500 mg of acetaminophen is contained in one tablet. If the tablet is large, it will be difficult to swallow and the feeling of taking it will be reduced. The acetaminophen content in one tablet may be in the range of 86 to 95% by weight, 86 to 94% by weight, 86 to 93% by weight, 86 to 92% by weight, 86 to 91% by weight, or 86 to 90% by weight. In this specification, containing acetaminophen at a high concentration means that the acetaminophen content in one tablet is high (for example, a content of 86% by weight or more).

[0021] In a specific embodiment of the present invention, the acetaminophen content in the tablet may be 90% by weight or more. In the case of producing a tablet containing 500 mg of acetaminophen per tablet, a content of 90% by weight or more may be particularly preferable.

[0022] The tablet of the present invention may have an acetaminophen content of 200 mg or more per tablet. Since 300 to 500 mg of acetaminophen is usually orally administered to adults at a time, if the content per tablet is 200 mg or more, it is practical to take 1 or 2 tablets at a time. The tablet of the present invention may have an acetaminophen content of 300 mg or more per tablet.

[0023] The tablet of the present invention has a density of 0.10 to 0.23 g / cm 3 The bulk density can be measured according to the method for measuring bulk density described in "The Seventeenth Revised Japanese Pharmacopoeia, 3. Methods for Measuring Powder Properties, 3.01 Method for Measuring Bulk Density and Tapped Density". There are many types of crystalline cellulose, and they are generally used for various purposes such as disintegrants, excipients, and binders. In the present invention, the bulk density is in the range of 0.10 to 0.23 g / cm. 3 Microcrystalline cellulose having a bulk density in the range of 0.10 to 0.23 g / cm can be used to improve tablet moldability. 3 Microcrystalline cellulose having a bulk density in the range of 0.10 to 0.23 g / cm3 can be said to have high moldability. 3 Microcrystalline cellulose having a bulk density in the range may be called highly moldable crystalline cellulose. The highly moldable crystalline cellulose used in the present invention may have an average particle size in the range of 20 to 100 μm. Furthermore, the highly moldable crystalline cellulose used in the present invention may have a high aspect ratio. This is because the crystalline cellulose is easily entangled due to its long and slender shape, and has good moldability. Examples of highly moldable crystalline cellulose products having such average particle size and bulk density include, but are not limited to, Ceolus (registered trademark) OD20-P and KG-1000 (Asahi Kasei Corporation). In one embodiment of the present invention, the average particle size is 0.10 to 0.15 g / cm. 3 It is preferable to use crystalline cellulose having a bulk density in the range of 1000 to 15000. Examples of crystalline cellulose products having a preferable bulk density include, but are not limited to, CEOLUS (registered trademark) KG-1000 (Asahi Kasei Corporation).

[0024] The tablet of the present invention can contain 7.3% or more by weight of highly moldable crystalline cellulose per tablet. By making the content of highly moldable crystalline cellulose in one tablet 7.3% by weight or more, a tablet having a tablet hardness that can sufficiently withstand impacts that may be received during manufacturing and distribution can be produced. The content of highly moldable crystalline cellulose in one tablet can be 7.3% by weight or more, for example, 7.4% by weight or more, 7.5% by weight or more, 7.6% by weight or more, 7.7% by weight or more, 7.8% by weight or more, 7.9% by weight or more, or 8.0% by weight or more. By making the content of highly moldable crystalline cellulose 7.3% by weight or more, even when acetaminophen is contained at a high concentration (for example, 86% by weight), a tablet having a hardness of 50N or more can be produced.

[0025] The upper limit of the content of highly moldable crystalline cellulose in one tablet is about 12% by weight. The tablet of the present invention contains acetaminophen at a high concentration of 86% by weight or more, so the content of other ingredients is limited. The content of highly moldable crystalline cellulose in one tablet can be 12% by weight or less, for example, 11.9% by weight or less, 11.8% by weight or less, 11.7% by weight or less, 11.6% by weight or less, 11.5% by weight or less, 11.4% by weight or less, 11.3% by weight or less, 11.2% by weight or less, 11.1% by weight or less, 11.0% by weight or less, 10.9% by weight or less, or 10.8% by weight or less. The content of highly moldable crystalline cellulose in one tablet can be, for example, in the range of 7.3% by weight to 12.0% by weight, 7.3% by weight to 11.9% by weight, 7.3% by weight to 11.8% by weight, 7.4% by weight to 12.0% by weight, 7.4% by weight to 11.9% by weight, 7.4% by weight to 11.8% by weight, 7.5% by weight to 12.0% by weight, 7.5% by weight to 11.9% by weight, or 7.5% by weight to 11.8% by weight.

[0026] The tablet of the present invention comprises at least two disintegrants, which may be selected from the group consisting of crospovidone, croscarmellose sodium, sodium starch glycolate, croscarmellose, sodium carboxymethyl starch, gelatin, starch, corn starch, low-substituted hydroxypropyl cellulose, and potato starch.

[0027] In a preferred embodiment of the present invention, the tablet comprises at least two disintegrants, the at least two disintegrants being at least one disintegrant (a) selected from the group consisting of crospovidone, croscarmellose sodium and sodium starch glycolate, and a disintegrant (b) which is low-substituted hydroxypropyl cellulose.

[0028] In the tablet of the present invention, the contents of the disintegrants (a) and (b) can be appropriately changed depending on the contents of the acetaminophen drug substance, the crystalline cellulose and the lubricant. The tablet of the present invention may contain, for example, 4.0% by weight or less, 3.9% by weight or less, 3.8% by weight or less, 3.7% by weight or less, 3.6% by weight or less, 3.5% by weight or less, 3.4% by weight or less, 3.3% by weight or less, 3.2% by weight or less, 3.1% by weight or less, 3.0% by weight or less, 2.9% by weight or less, 2.8% by weight or less, 2.7% by weight or less, 2.6% by weight or less, 2.5% by weight or less, 2.4% by weight or less, 2.3% by weight or less, 2.2% by weight or less, 2.1% by weight or less or 2.0% by weight or less of disintegrants (a) and (b) in total, and may further contain 1.0% by weight or more, 1.1% by weight or more, further 1.2% by weight or more, further 1.3% by weight or more, 1.4% by weight or more or 1.5% by weight or more. The range of the total content of the disintegrants (a) and (b) can be, for example, a total range of 1.0 to 4.0% by weight, a total range of 1.0 to 3.5% by weight, or a total range of 1.0 to 3.0% by weight, but is not limited thereto. The total content of the disintegrants (a) and (b) can be appropriately changed, particularly depending on the content of the acetaminophen drug substance and the crystalline cellulose, so as to satisfy the dissolution standard of 80% or more of 15-minute dissolution rate and / or to improve storage stability. The dissolution test can be measured based on the dissolution test method described in the 17th revised Japanese Pharmacopoeia, and the 15-minute dissolution rate is the dissolution rate 15 minutes after the start of the test. More specifically, it can be measured based on the general test method of the Japanese Pharmacopoeia, the second method of the dissolution test method (paddle method).

[0029] The present inventors have surprisingly found that the dissolution standard of 80% or more in 15 minutes is satisfied by containing at least two disintegrants (a) and (b) in combination, rather than one of them. Specifically, as shown in the examples below, the dissolution standard of 80% or more in 15 minutes can be satisfied by containing at least one disintegrant (a) selected from the group consisting of crospovidone, croscarmellose sodium, and sodium starch glycolate, and the disintegrant (b) which is low-substituted hydroxypropyl cellulose in combination. By satisfying the dissolution standard of 80% or more in 15 minutes, it is expected that the antipyretic and analgesic effect of acetaminophen will be rapidly developed. On the other hand, it has been revealed that tablets containing only crospovidone or tablets containing only low-substituted hydroxypropyl cellulose do not satisfy the dissolution standard of 80% or more in 15 minutes.

[0030] The tablet of the present invention may contain at least two kinds of disintegrants (a) and (b) in a specific ratio. The ratio of disintegrant (a) in the total of disintegrants (a) and (b) contained in one tablet of the present invention may be 15 to 95% by weight, preferably 20 to 90% by weight, more preferably 20 to 80% by weight, and even more preferably 30 to 80% by weight.

[0031] The tablet of the present invention may further contain a dispersant. The dispersant is preferably hydrated silicon dioxide or light anhydrous silicic acid. The blending ratio of the dispersant may be 0.1 to 2% by weight relative to 100% by weight of the preparation.

[0032] The tablet of the present invention may further contain a lubricant. The lubricant is preferably magnesium stearate. The blending ratio of the lubricant may be 0.1 to 2% by weight based on 100% by weight of the preparation.

[0033] Regarding tablet hardness, it is generally believed that a tablet having a hardness of 50N or more can withstand, for example, the impact when packaging the tablet in a PTP or the like, the impact during transportation, and the force during handling by a patient. The tablet of the present invention has a tablet hardness of 50N or more, and may be 51N or more, 52N or more, 53N or more, 54N or more, 55N or more, 56N or more, 57N or more, 58N or more, 59N or more, or 60N or more. In the present invention, there is no particular limit to the upper limit of the tablet hardness, but it may be 150N or less, or 100N or less. The tablet hardness can be measured using a load cell type tablet hardness meter (PC-10, Okada Seiko Co., Ltd.) or the like.

[0034] The tablet of the present invention can have an acetaminophen dissolution rate of 80% or more in 15 minutes, preferably an acetaminophen dissolution rate of 85% or more in 15 minutes, and more preferably an acetaminophen dissolution rate of 90% or more in 15 minutes.

[0035] The tablet of the present invention may further contain additives other than the highly moldable crystalline cellulose, disintegrant, dispersant and lubricant (hereinafter, other additives). Examples of other additives include excipients such as D-mannitol and lactose, flow agents such as anhydrous silicon dioxide, calcium silicate, silicic acid dihydrate and magnesium aluminometasilicate, stabilizers such as cyclodextrin, colorants, etc., but are not limited thereto, and general additives used in pharmaceutical manufacturing can be used. When a flow agent is contained, it can be contained in the range of 0.1 to 1.0% by weight per tablet.

[0036] The size of the tablet of the present invention may be, but is not limited to, a diameter in the range of 6 mm to 18 mm, an aspect ratio in the range of 1 to 3, and a thickness in the range of 2 mm to 10 mm. The shape of the tablet of the present invention may be a normal tablet or an irregular tablet, for example, a circular, oval, or caplet shape, but is not limited to these.

[0037] (Tablet manufacturing method) Another aspect of the present invention is a pharmaceutical composition comprising acetaminophen having a median particle size in the range of 100 to 350 μm and a pharmaceutical composition having a median particle size of 0.10 to 0.23 g / cm 3 and mixing at least two disintegrants to obtain a powder mixture; directly compressing the powder mixture to obtain tablets; The present invention relates to a method for producing the above tablet, wherein the at least two disintegrants are at least one disintegrant (a) selected from the group consisting of crospovidone, croscarmellose sodium and sodium starch glycolate, and a disintegrant (b) which is low-substituted hydroxypropyl cellulose.

[0038] The manufacturing method of the present invention "contains acetaminophen having a median particle size in the range of 100 to 350 μm and an average particle size of 0.10 to 0.23 g / cm 3 The "process of mixing crystalline cellulose having a bulk density in the range of 0.1 to 100 μg / g with at least two kinds of disintegrants to obtain a powder mixture" (hereinafter referred to as the "mixing process") is a process of mixing the physiologically active drug acetaminophen of the tablet with other ingredients before tableting. The other ingredients are the highly moldable crystalline cellulose, the disintegrant, and other additives.

[0039] The acetaminophen having a median particle size in the range of 100 to 350 μm, the highly moldable crystalline cellulose, the disintegrant and other additives used in the manufacturing method of the tablet of the present invention may be the same as those described in the above section (Tablets).

[0040] In this specification, "mixing" means mixing two or more types of powder. The term "pulverization" is used in the field, which means crushing particles to obtain small particles. On the other hand, "mixing" in this specification is an operation that does not have the effect of reducing the particle size of the powder. Also, "disintegration and sizing" used in the field means peeling off aggregated particles. In disintegration and sizing and crushing, a strong "shear force" is applied to the powder, but mixing is an operation with a weak "shear force". For example, in the case of a powder in which many acetaminophen particles in the fine powder region are aggregated, a strong "shear force" is required to peel off each particle, and this operation is disintegration and sizing. An operation that breaks down particles with an even stronger "shear force" is called crushing.

[0041] The mixing step of the present manufacturing method can be carried out, for example, using a V-type mixer or a container mixer. A V-type mixer is a device that rotates a V-shaped mixing container to move the powder particles in the container throughout and impart convection motion, thereby performing rapid and uniform mixing. By using a V-type mixer, it is usually possible to perform gentle mixing without applying excessive force to the powder particles. The mixing conditions can be appropriately changed depending on the scale, but can be carried out, for example, at a rotation speed of 5 to 50 rpm for about 1 to 15 minutes.

[0042] The mixing step of the present manufacturing method may be performed in one mixing operation, or may be performed in two or more separate mixing operations. When performing the mixing step in one operation, all the components contained in the tablet are charged into a V-type mixer or the like and mixed. When performing the mixing step in two or more separate operations, the components contained in the tablet can be charged into a V-type mixer or the like in two or more separate batches according to type and mixed. For example, in the first mixing, the components other than the lubricant (e.g., magnesium stearate) and the dispersant (e.g., hydrated silicon dioxide or light anhydrous silicic acid) are charged into a V-type mixer or the like and mixed, and the lubricant and the dispersant are added after the first mixing and mixed again. This can prevent the lubricant and the dispersant from spreading. The mixing after adding the lubricant and the dispersant can be performed for about 1 to 3 minutes. A powder mixture can be obtained by the mixing step of the present manufacturing method. The powder mixture is a powdery aggregate of the components contained in the tablet. In addition, in the manufacturing method of the present invention, it is not necessary to adjust the moisture content by adding water or the like.

[0043] The "step of directly compressing the powder mixture to obtain tablets" (hereinafter referred to as the tableting step) in the production method of the present invention is a step of directly compressing the powder mixture obtained in the mixing step to form tablets. In this specification, direct tableting refers to tableting by a dry method in which the powder mixture is directly compressed using a punch and die to obtain tablets.

[0044] Specifically, tableting can be carried out using a tablet press (e.g., a rotary molding machine), for example, by weighing the volume of powder filled in a fixed mold (mortar cavity), compressing and molding it using upper and lower molds (pestles), and finally releasing it from the mold (mortar cavity).

[0045] In the manufacturing method of the present invention, the tableting pressure can be appropriately set in consideration of the tablet hardness and the pressure tolerance of the tableting punch, and can be in the range of 3 to 50 kN, preferably 5 to 40 kN. The tableting pressure imparts physical strength such as hardness to the tablet, and a low tableting pressure may result in a low tablet hardness. However, increasing the tableting pressure does not necessarily increase the tablet hardness. For example, depending on the ingredients, the tablet hardness may not increase even if the tableting pressure is increased. In addition, high tableting pressure is likely to cause damage to the tableting punch or tableting problems (capping, sticking). Therefore, during tableting, it is necessary to apply a pressure according to the characteristics of the tablet.

[0046] In the manufacturing method of tablets, wet methods such as fluidized bed granulation are often used. However, wet granulation requires many steps and the manufacturing cost is relatively high. According to the present invention, a method of directly compressing powder can be provided to manufacture tablets simply and at low manufacturing cost. In addition, since it does not include a step of adding water, there is little risk of contamination due to contamination. EXAMPLES

[0047] The present invention will be described in more detail with reference to the following examples, but the present invention is not limited to these examples. In this specification, unless otherwise specified, "%" is based on weight, and numerical ranges are described as including their endpoints.

[0048] Materials and Methods (1) Material In the following examples and comparative examples, tablets containing acetaminophen were prepared using the following reagents: Acetaminophen (AA) drug substance a) Acetaminophen S (Yamamoto Chemical Industry Co., Ltd.) (hereinafter referred to as AA drug substance a) b) Acetaminophen H (Yatsushiro Pharmaceutical Co., Ltd.) (hereinafter referred to as AA drug substance b) c) Dense Powder (SpecGx LLC) (hereinafter referred to as AA bulk drug c) d) crystals (granules) (hereinafter referred to as AA drug substance d) e) Acetaminophen SS (Yamamoto Chemical Industry Co., Ltd.) (hereinafter referred to as AA drug substance e) f) Acetaminophen J grade (Anqiu Lu'an Pharmaceutical Co., Ltd.) (hereinafter referred to as AA drug substance f) g) Acetaminophen (Iwaki Pharmaceutical Co., Ltd.) (hereinafter referred to as AA drug substance g) Crospovidone (CL-F, BASF) Sodium starch glycolate (Primojel, DEF pharma) Croscarmellose sodium (Kiccolate® ND-200, Asahi Kasei Corporation) Low-substituted hydroxypropyl cellulose (LH-11, Shin-Etsu Chemical Co., Ltd.) Microcrystalline cellulose (CEOLUS® KG-1000, Asahi Kasei Corporation) Magnesium stearate (Taihei Chemical Industry) Hydrated silicon dioxide (Carplex #80, Evonik Japan Co., Ltd.)

[0049] (2) Manufacturing method The manufacturing method of the tablets is as follows. First, AA drug substance, crospovidone, low-substituted hydroxypropyl cellulose and microcrystalline cellulose were mixed and stirred in a V-type mixer (rotation speed 42 rpm, mixing time 10 minutes) to obtain intermediate tableting powder. Magnesium stearate and hydrated silicon dioxide were added to the intermediate tableting powder, and further mixed and stirred (rotation speed 42 rpm, mixing time 2 minutes) to obtain tableting powder. The tableting powder was compressed using a tableting machine and a punch and die with a diameter of 9 mm to obtain tablets.

[0050] A V-type mixer (V-10, Tokuju Manufacturing) was used to mix the powder for tableting, and a tablet press (HT-AP15SS-II, Hata Iron Works) and flat-corner punches and dies were used for tableting. When tableting was possible, the tableting pressure was set so that the tablet hardness would be 50N or more, taking into consideration the pressure tolerance of the tableting punch.

[0051] (3) Particle size measurement of acetaminophen drug substance Dry particle size measurement was performed on the acetaminophen drug substance using the laser diffraction method. A Laser Micron Sizer LMS-2000e (Seishin Enterprise Co., Ltd.) was used to measure the particle size distribution. The dispersion compressed air pressure during the measurement was 0.5 bar.

[0052] (4) Tablet hardness measurement A hardness measurement test was carried out on the tablets produced in the examples described below. The hardness measurement was carried out using a hardness tester (PC-30, Okada Seiko).

[0053] (5) Tablet dissolution test A dissolution test was carried out on the tablets (acetaminophen content 300 mg / tablet) produced in the Examples described below. The dissolution test was carried out according to the method 2 (paddle method) of the General Tests and Dissolution Tests of the Japanese Pharmacopoeia, 17th Edition. The test liquid used was water according to the General Tests and Disintegration Tests of the Japanese Pharmacopoeia. The test was carried out using a dissolution tester (RT-J2000, DS-3, Dai Nippon Seiki) and a spectrophotometer (UV-1000, Shimadzu Corporation).

[0054] Specifically, one test tablet was placed in 900 mL of test liquid kept at a liquid temperature of 37±0.5°C, and the dissolution test was started at 50 revolutions per minute. After that, 10 mL of the dissolution liquid was collected at specified time intervals and filtered through a 0.45 μm pore size surface filter to obtain a sample solution. 2 mL of the sample solution was placed in a 100 mL measuring flask for dilution, and 4 mL of the dilution liquid was placed in a 100 mL measuring flask for dilution. The dissolution rate was measured with a spectrophotometer (measurement wavelength: 243 nm) and calculated. When the dissolution rate in 15 minutes was 80% or more, it was determined that the dissolution standard was met.

[0055] <Example 1: Study on particle size and dissolution rate of acetaminophen (AA) drug substance> The particle size measurements of seven types of AA drug substances are shown in Table 1. [Table 1]

[0056] Next, five types of AA drug substances a to e were used to manufacture tablets with the composition and conditions shown in Table 2. Furthermore, a dissolution test was performed on each tablet. When AA drug substance e was used, it was not possible to manufacture a tablet containing 300 mg (90%) of the AA drug substance and having a tablet weight of 333 mg, even when the maximum pressure of the tablet press was applied. This is thought to be because AA drug substance e is bulky.

[0057] [Table 2] Tablets A1, A2 and A3 manufactured using AA drug substance a, tablet B manufactured using AA drug substance b, and tablet C manufactured using AA drug substance c met the dissolution standard (dissolution rate of 80% or more in 15 minutes). On the other hand, tablets D1 and D2 manufactured using AA drug substance d did not meet the dissolution standard. This example revealed that the average particle size of the AA drug substance used in the manufacture of tablets has an effect on the dissolution rate and acetaminophen content of the tablets. In Example 7 described later, tablets that meet the dissolution standard can be manufactured using drug substances f and g. Therefore, it is considered that the range of the average particle size of the AA drug substance suitable for the manufacture of the tablets of the present invention is a median particle size range of 100 to 350 μm.

[0058] Figure 1 shows the dissolution curves of tablets A1 and B listed in Table 2. Tablets A1 and B have different types of AA drug substance and different blend ratios of disintegrant and crystalline cellulose, but they have similar dissolution characteristics. It is believed that the dissolution characteristics can be optimized by changing the blend ratio of disintegrant and crystalline cellulose. Both tablets A1 and B were compressed at a compression pressure of 20 kN.

[0059] <Example 2: Study on the amount of disintegrant added and dissolution rate> The amount of two types of disintegrants and their dissolution rates were examined. Tablets A4 to A8 were manufactured using AA drug substance a according to the composition in Table 3. Tablets A4 to A8 have different blend ratios of the disintegrants crospovidone and low-substituted hydroxypropyl cellulose. Tablets A4 to A8 contain 90% acetaminophen, but can be directly compressed. Furthermore, a dissolution test was performed on each tablet. [Table 3]

[0060] Tablet A4 contained only low-substituted hydroxypropylcellulose as a disintegrant, but the 15-minute dissolution rate was 56%, which did not meet the dissolution standard.Tablet A8 contained only crospovidone as a disintegrant, but the 15-minute dissolution rate was 41%, which did not meet the dissolution standard.

[0061] Tablet A5 contained about 53.8% crospovidone in the disintegrant, and the 15-minute dissolution rate was 87%, which met the dissolution standard. Tablet A6 contained about 84.6% crospovidone in the disintegrant, and the 15-minute dissolution rate was 89%, which met the dissolution standard. Tablet A7 contained about 92.3% crospovidone in the disintegrant, and the 15-minute dissolution rate was 83%, which met the dissolution standard. Furthermore, tablet A1 of Example 1 contained about 35.7% crospovidone in the disintegrant, and the 15-minute dissolution rate was 98%, which met the dissolution standard. Tablet A2 of Example 1 contained about 46.7% crospovidone in the disintegrant, and the 15-minute dissolution rate was 99%, which met the dissolution standard. Tablet A3 of Example 1 contained about 73.3% crospovidone in the disintegrant, and the 15-minute dissolution rate was 82%, which met the dissolution standard. Tablet B of Example 1 contained about 16.7% crospovidone in the disintegrant, and the 15-minute dissolution rate was 99%, satisfying the dissolution standard.

[0062] A graph of the crospovidone ratio in the disintegrant and the 15-minute dissolution rate is shown in Figure 2. It was confirmed that the 15-minute dissolution rate changed by changing the blending ratio of crospovidone to low-substituted hydroxypropyl cellulose.

[0063] Example 3: Study of acetaminophen content Using AA drug substance a, each tablet was manufactured according to the composition in Table 4. Tablets A90-1 to A90-5, A70-1 to A70-5, and A50-1 to A50-5 shown in Table 4 have different blend ratios of acetaminophen and the disintegrants crospovidone and low-substituted hydroxypropylcellulose. All tablets shown in Table 4 were directly compressible. Furthermore, a dissolution test was performed on each tablet.

[0064] Table 4 summarizes the composition and properties of the tablets. [Table 4] As shown in Figure 3, the dissolution rate changed depending on the blending ratio of the active pharmaceutical ingredient and the blending ratio of the disintegrant.

[0065] <Example 4: Study on acetaminophen content 2> Using AA bulk drug a, tablets were manufactured according to the composition in Table 5. All tablets listed in Table 5 were directly compressible. Furthermore, each tablet was subjected to a dissolution test. Table 5 shows the composition and properties of the tablets. [Table 5]

[0066] Tablets A80, A85, A86, A87, A88 and A89 contain different acetaminophen content ratios. The dissolution rate changed dramatically between 85% and 86% AA API content.

[0067] <Example 5: Examination of types of disintegrants> Each tablet was manufactured using AA drug substance a according to the composition in Table 6. Tablets 11 and 12 shown in Table 6 were manufactured using croscarmellose sodium or sodium starch glycolate instead of crospovidone. All tablets shown in Table 6 were directly compressible. Furthermore, each tablet was subjected to a dissolution test. Table 6 shows the composition and properties of the tablets. [Table 6]

[0068] Tablets made using croscarmellose sodium or sodium starch glycolate instead of crospovidone were directly compressible and met dissolution rate specifications.

[0069] <Example 7: Study on the content of disintegrant> Each tablet was manufactured using AA drug substance f or g according to the composition in Table 7. Tablets F1 to F4 shown in Table 7 were manufactured using drug substance f, and the total amount of two types of disintegrants was changed between 1.0% and 3.0%. Tablet G was manufactured using drug substance g, and the total amount of two types of disintegrants was 3.0%. All tablets listed in Table 7 were directly compressible. Furthermore, a dissolution test was performed on each tablet. Table 7 shows the composition and properties of the tablets. [Table 7] All tablets listed in Table 7 were directly compressible and met dissolution rate specifications.

Claims

1. acetaminophen having a median particle size in the range of 100 to 350 μm; 0.10~0.23g / cm 3 Microcrystalline cellulose having a bulk density in the range of and at least two disintegrants, At least two disintegrants At least one disintegrant (a) selected from the group consisting of crospovidone, croscarmellose sodium and sodium starch glycolate; and A disintegrant (b) which is low-substituted hydroxypropyl cellulose; A tablet having an acetaminophen content of 86% by weight or more per tablet.

2. The tablet according to claim 1, having a tablet hardness of 50 N or more.

3. The tablet according to claim 1 or 2, wherein each tablet contains 7.3% by weight or more of the crystalline cellulose.

4. The tablet according to any one of claims 1 to 3, wherein the ratio of the disintegrant (a) to the at least two types of disintegrants contained in one tablet is 15 to 95% by weight.

5. The tablet according to any one of claims 1 to 4, wherein each tablet contains 1.0 to 4.0% by weight of the disintegrants (a) and (b) in total.

6. The tablet according to any one of claims 1 to 5, wherein the dissolution rate of acetaminophen is 80% or more in 15 minutes.

7. acetaminophen having a median particle size in the range of 100 to 350 μm; 0.10~0.23g / cm 3 Microcrystalline cellulose having a bulk density in the range of with at least two disintegrants to obtain a powder mixture; and directly compressing the powder mixture to obtain tablets; At least two disintegrants At least one disintegrant (a) selected from the group consisting of crospovidone, croscarmellose sodium and sodium starch glycolate; and The method for producing a tablet according to any one of claims 1 to 6, wherein the disintegrant (b) is low-substituted hydroxypropyl cellulose.

Citation Information

Patent Citations

  • Method for producing formulation

    JP2013216610A

  • Tablet with high drug content and production method thereof

    JP2015063521A

  • Stable production method of high drug content compressed tablet

    JP2017210478A

  • Orally disintegrating tablet, and production method of the same

    JP2018058910A

  • Method for producing acetaminophen preparation

    JP2018090638A